SS148 and WZ16 inhibit the activities of nsp10-nsp16 complexes from all seven human pathogenic coronaviruses - Li, Fengling; Ghiabi, Pegah; Hajian, Taraneh; Klima, Martin; Li, Alice Shi Ming; Khalili Yazdi, Aliakbar; Chau, Irene; Loppnau, Peter; Kutera, Maria; Seitova, Almagul; Bolotokova, Albina; Hutchinson, Ashley; et al. (Biochimica et biophysica acta. General subjects, 2023)
Seven coronaviruses have infected humans (HCoVs) to-date. SARS-CoV-2 caused the current COVID-19 pandemic with the well-known high mortality and severe socioeconomic consequences. MERS-CoV and SARS-CoV caused epidemic of MERS and SARS, respectively, with severe respiratory symptoms and significant fatality. However, HCoV-229E, HCoV-NL63, HCoV-HKU1, and HCoV-OC43 cause respiratory illnesses with less severe symptoms in most cases. All coronaviruses use RNA capping to evade the immune systems of humans. Two viral methyltransferases, nsp14 and nsp16, play key roles in RNA capping and are considered valuable targets for development of anti-coronavirus therapeutics. But little is known about the kinetics of nsp10-nsp16 methyltransferase activities of most HCoVs, and reliable assays for screening are not available. Here, we report the expression, purification, and kinetic characterization of nsp10-nsp16 complexes from six HCoVs in parallel with previously characterized SARS-CoV-2. Probing the active sites of all seven by SS148 and WZ16, the two recently reported dual nsp14 / nsp10-nsp16 inhibitors, revealed pan-inhibition. Overall, our study show feasibility of developing broad-spectrum dual nsp14 / nsp10-nsp16-inhibitor therapeutics.
Keywords: Enzyme kinetics; Viral protein; Enzyme purification; methyltransferasy; COVID-19; Pandemics; RNA methyltransferase; Humans; nsp10-nsp16 complex; pandemie; RNA virus; Coronavirus; Methyltransferases; SARS-CoV-2; lidé; RNA